Polyads types of the mimosoid clade (Caesalpinioideae, Fabaceae): size and pollen numbers variations - Soares, Eduardo Lopes; Landi, Lorrayne Albernaz Domingues Camilo; Souza, Cintia Neves De; Gasparino, Eduardo Custódio [UNESP] (Taylor & Francis, 2022)
The pollen morphology of 17 species and three varieties of the native mimosoid clade of forest fragments of the Cerrado (Brazilian savanna) was studied in order to expand the knowledge on the morphology of genera and species of this group, in particular on the morphology of polyads, as well as add information to pollen studies for species of Caesalpinioideae occurring in the area. The pollen grains were acetolysed, measured, described qualitatively and illustrated under light microscopy and scanning electron microscopy (not acetolysed pollen grains). Pollen metric data were examined by descriptive and multivariate analysis. The studied species showed differences on the pollen units (monads or polyads) and variations in number and distribution of pollen grains in the polyads. Three pollen types were observed: type I, pollen grains in monads (Plathymenia reticulata); type II, polyads with one tapered end (drop shape–Calliandra parviflora); type III, polyads with uniform ends with asymmetrically distributed pollen grains (Stryphnodendron species); or symmetrically (with 16 or 20 pollen grains in Acacia plumosa, Albizia niopoides, Anadenanthera species, Inga marginata, Inga vera and Senegalia species and more than 20 pollen grains in Enterolobium contortisiliquum, Inga edulis and Inga sessilis). The qualitative differences and the measuremets of the diameters of the polyads, made it possible to distinguish the taxa and to confirm the eurypalynous character of the mimosoid clade (Caesalpinioideae, Fabaceae).
Keywords: Brazil; eurypalynous; hierarchical cluster analysis (HCA); Leguminosae; palynology; principal component analysis (PCA)